Fresh cheese as a vehicle for polyunsaturated fatty acids integration: effect on physico-chemical, microbiological and sensory characteristics. (3rd October 2017) - Dal Bello, Barbara; Torri, Luisa; Piochi, Maria; Bertolino, Marta; Zeppa, Giuseppe
Abstract: Five different vegetable oils were used in the production of fresh cheese to increase the concentration of polyunsaturated fatty acids (PUFAs), particularly α-linolenic acid (ALA), the most important omega-3 fatty acid of vegetable origin. Physico-chemical and microbiological characteristics of functionalized cheeses were evaluated after 1 and 3 days of ripening at 4 °C while the consumer appreciation was evaluated in the final product at 3 days of ripening. After 3 days, the cheeses with Camelina sativa and Echium plantagineum oils added exhibited the highest retention of PUFAs (mostly ALA) compared to those with flaxseed, raspberry and blackcurrant oils. The addition of oil showed little effects on physico-chemical characteristics and also consumers' evaluation highlighted that all of the fresh cheeses were considered acceptable although those with flaxseed and raspberry oils were the most appreciated.